Suspicions of Occult Medicine Murders in Context of Democratic Elections in Contemporary Côte d’Ivoire - Syna Ouattara (European Scientific Journal, ESJ, 2024)
The article aims to contribute to contemporary discourses on so-called occult medicine practices and the associated human murders within the context of democratic elections in Côte d’Ivoire. The study is grounded in anthropological fieldwork conducted in Abidjan from 2018 to 2020. Additionally, information on occult medicine murders from local and international media has been gathered to further enrich the reflections. The study reveals that in the prevalent public discourse, politicians are accused of employing occult medicine to enhance their power and ensure their success by collaborating with ritual specialists. The paper argues that, in everyday discourse, occult medicine murders can be perceived as being ontologically motivated.